2006
DOI: 10.4012/dmj.25.669
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alumina-blasting and Adhesive Primers on Bonding between Resin Luting Agent and Zirconia Ceramics

Abstract: This study evaluated the effect of alumina-blasting and three commercial adhesive primers on the shear bond strength of a dual-cured resin luting agent to zirconia ceramics. Two different-sized zirconia ceramic specimens were treated with or without alumina-blasting and then treated with one of three adhesive primers. Subsequently, specimens were cemented together with Linkmax HV(GC) . Half of the specimens were stored in water at 37℃ for 24 hours and the other half thermocycled 10,000 times before shear bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
3
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 28 publications
9
80
3
9
Order By: Relevance
“…Therefore, excessive surface roughness due to alumina-blasting is not necessary to increase bond strength. These findings are similar to those reported in a previous study, which found that surface roughness was not the only factor in bond strength 31) . Increasing the pressure of alumina-blasting would increase the surface roughness of zirconia frameworks.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, excessive surface roughness due to alumina-blasting is not necessary to increase bond strength. These findings are similar to those reported in a previous study, which found that surface roughness was not the only factor in bond strength 31) . Increasing the pressure of alumina-blasting would increase the surface roughness of zirconia frameworks.…”
Section: Discussionsupporting
confidence: 82%
“…The present study revealed that the shear bond strength of EP on ASB was significantly higher (p<0.05) than that of ASB without primer at 24 h. These results suggested that ASB treatment contributed not only to an increase in mechanical retention, but also to the cleaning and activation effects for Y-TZP [33][34][35] . ASB treatment alone barely achieved high bond strength after 30,000 thermal cycles.…”
Section: Discussionsupporting
confidence: 53%
“…Both the penetration of the resin cement and in situ polymerization are responsible for the bonding of the resin cement to the ceramic restorations [34]. According to Tsuo et al, recommended air-borne particle size for sintered zirconia is 50 m [20]. Another study concluded that air-borne particle abrasion with either smaller (50 m) or larger (110 m) particles is of beneficial for zirconia with a machined surface in terms of shear bond strength [21,35].…”
Section: Discussionmentioning
confidence: 99%
“…1 [20,21]. All specimens were cleaned ultrasonically with distilled water in 5 min and rinsed for 1 min.…”
Section: Preparations Of the Specimensmentioning
confidence: 99%